Implementing long‐term baselines into primate tool‐use studies - Bandini, Elisa (American journal of primatology, 2021)
Studies on primate tool‐use often involve the use of baseline conditions, as they allow for the examination of any differences in the subjects' behavior before and after the introduction of a tool‐use task. While these baseline conditions can be powerful for identifying the relative contributions of individual and social learning for the acquisition of tool‐use behaviors in naïve (usually captive) subjects, many have criticized them for being too short, and not allowing enough time for the behavior to develop spontaneously. Furthermore, some wild tool‐use behaviors such as chimpanzee nut‐cracking require animals to manipulate and familiarize themselves with the materials of the behavior within a “sensitive learning period” before it develops later on in life. One solution to this problem is to implement long‐term baselines, in which, with collaboration with zoological institutions, the materials of the behavior are left in the enclosure for an extended period. The keepers would then be asked not to demonstrate or train the animals in the target behavior, but to report back to the researchers if they observe the behavior emerge during this extended period. Alongside keeper reports, video cameras could be installed in the enclosure to minimize the chance of false negatives and to allow for coding and inter‐rater reliability to be carried out on the videos. These long‐term baselines therefore provide extended enrichment opportunities for the animals, alongside allowing the zoological institution to publicize their involvement with the study and guests to observe animals interacting with different testing apparatuses and tools. Finally, long‐term baselines can provide invaluable insight on the individual and social learning abilities of primates as well as the potential development stages and sensitive learning periods required for specific behaviors. Studies on the learning mechanisms behind primate behaviors have been criticized for not allowing enough time for subjects to spontaneously develop the target behaviors. In collaboration with animal keepers, long‐term baselines can provide a solution to this problem. In long‐term baselines, all the materials of the behavior are left in the animals' enclosure for an extended period, and keepers are asked to report back to the researchers if the behavior emerges, therefore allowing time for the behavior to develop. Research Highlights One way to identify the learning mechanisms behind primate behaviors is to provide naïve subjects with all the materials of a target behavior without any demonstrations. This condition is known as a “baseline” in the literature. Researchers have criticized baselines for being too short, and not allowing enough time for behaviors to develop individually. Long‐term baselines provide one solution to this problem as they involve giving all the materials of the target behavior to naïve subjects for an extended period. The keepers are then asked to report back to the researchers if they observe the behavior develop while continuing their daily routines. Long‐term baselines can be implemented with minimal costs and investment of the keepers and researchers. In return, they can provide valuable information on the individual learning abilities of primates, data that might otherwise be lost in shorter baseline conditions.